YKL-40 Is Elevated in Cerebrospinal Fluid from Patients with Purulent Meningitis - Østergaard, Christian (American Society for Microbiology, 2002)
YKL-40, a member of the family 18 glycosyl hydrolases, is secreted by activated neutrophils and macrophages. It is a growth factor for connective tissue cells and a potent migration factor for endothelial cells and may function in inflammation and tissue remodeling. YKL-40 was determined in 134 cerebrospinal fluid (CSF) samples taken on admission from patients suspected of having meningitis (48 with purulent meningitis, 49 with lymphocytic meningitis, 5 with encephalitis, and 32 without evidence of meningitis). YKL-40 levels in CSF were significantly higher in patients with purulent meningitis (median, 663 μg/liter [range, 20 to 8,960]) and encephalitis (5,430 μg/liter [620 to 11,600]) than in patients with lymphocytic meningitis (137 μg/liter [41 to 1,865]) or patients without meningitis (167 μg/liter [24 to 630]) (Kruskal-Wallis and Dunn multiple comparison tests, P < 0.001). CSF YKL-40 levels were also determined for 26 patients with purulent meningitis having a repuncture, and patients who died (n = 5) had significantly higher YKL-40 levels than patients who survived (n = 21) (2,100 μg/liter [1,160 to 7,050] versus 885 μg/liter [192 to 15,400], respectively; Mann-Whitney test, P = 0.018). YKL-40 was most likely locally produced, since patients with infections of the central nervous system had CSF YKL-40 levels that were at least 10-fold higher than the corresponding levels in serum (2,033 μg/liter [470 to 11,600] versus 80 μg/liter [19 to 195]). The CSF neopterin level was the biochemical parameter in CSF and blood that correlated best with CSF YKL-40 levels, indicating that YKL-40 may be produced by activated macrophages within the central nervous system. In conclusion, high levels of YKL-40 in CSF are found in patients with purulent meningitis.